2016
DOI: 10.1186/s12877-016-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between benzodiazepine use and sleep quality in residential aged care facilities: a cross-sectional study

Abstract: BackgroundBenzodiazepines are commonly prescribed in residential aged care facilities (RACFs) for their sedative and anxiolytic effects. The objective of this study was to investigate the association between benzodiazepine use and sleep quality in residents of RACFs.MethodsA cross-sectional study involving 383 participants was conducted in six Australian RACFs. Night-time sleep quality, day-time drowsiness and day-time napping behavior were assessed using a validated questionnaire. Logistic regression was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…Next, patients with depression and/or anxiety may be treated by sedative drugs, which may increase their ability to nap. In a group of institutionalized elderly individuals in Australia, the use of benzodiazepines was associated with longer daytime napping (OR = 1.77) 43 . Patients with depression may also feel that napping reduced the severity of their symptoms and thus improved their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Next, patients with depression and/or anxiety may be treated by sedative drugs, which may increase their ability to nap. In a group of institutionalized elderly individuals in Australia, the use of benzodiazepines was associated with longer daytime napping (OR = 1.77) 43 . Patients with depression may also feel that napping reduced the severity of their symptoms and thus improved their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…33 Several recent studies have shown that long term BZD use for insomnia is associated with worsening sleep quality, including difficult falling asleep and more nighttime awakenings, as compared to non-users. 3437 Clinicians may consider use of non-benzodiazepine receptor agonist (“Z-drugs”) as a safer alternative, however, studies demonstrate a similar concerning side effect profile for use in older adults including increased risk of falls, 38 fracture, 39 impaired cognition, 31 and motor vehicle accidents 40 due to morning after impairment. In addition, a variety of newer studies have established that CBT is an effective treatment for insomnia, if not more effective than BZD and sedative hypnotics in a general adult population, 41,42 yet without any of the associated potential risks.…”
Section: Discussionmentioning
confidence: 99%
“…High doses of many short-acting benzodiazepines can also cause pre and post-mortem memory loss and dissociation. This property makes benzodiazepines useful for treating insomnia, anxiety, agitation, seizures, alcohol withdrawal, muscle spasms, and medication before medical or dental procedures (Chen et al ., 2016). Benzodiazepines are classified as having short-term, intermediary, or long-term behaviors.…”
Section: Sex Differences In the Efficacy Of Therapeutics For Sleep DImentioning
confidence: 99%